2007
DOI: 10.1080/00103620701588312
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Geochemistry of Arsenic in Groundwater of Punjab, Northwest India

Abstract: Arsenic (As) is a deadly poison at high concentrations. It is mysterious in the sense that people are exposed to it most of the time through drinking groundwater, fortunately at much lower concentrations than the deadly levels, and usually without knowing it. Arsenic content in alluvial aquifers of Punjab varied from 3.5 to 688 mg L 21 . Arsenic status of groundwater is classified into low (,10 mg L 21 ), moderate (!10 to ,25 mg L 21 ), high (!25 to ,50 mg L 21 ), and very high (.50 mg L 21 ). In zone I, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 31 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…However, it is important to mention here that these water samples were taken from Zone I and II which fulfill all the parameters suitable for good quality of water set by public health department since the arsenic content is not included in their tests. Hundal et al (2007) reported that the As concentration ranged from 11.4 to 688 ppb with average value of 76.8 ppb. In the aridic southwest, zone III, all water samples contained As concentrations much greater than the safe limit and thus were not suitable for drinking purposes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it is important to mention here that these water samples were taken from Zone I and II which fulfill all the parameters suitable for good quality of water set by public health department since the arsenic content is not included in their tests. Hundal et al (2007) reported that the As concentration ranged from 11.4 to 688 ppb with average value of 76.8 ppb. In the aridic southwest, zone III, all water samples contained As concentrations much greater than the safe limit and thus were not suitable for drinking purposes.…”
Section: Resultsmentioning
confidence: 98%
“…Arsenic in ground water is largely the result of minerals dissolving from weathered rocks and soils. The underground waters contain elevated arsenic concentration, which are usually above the WHO (1996) permissible safe limits of 10 ppb (Hundal et al 2007). The problem is more severe at several sites in south-western districts of Punjab where the arsenic concentration exceeded more than 20 to 30 folds of the WHO safe limit.…”
Section: Introductionmentioning
confidence: 99%
“…According to Central Ground Water Board (2007), the groundwater in Bathinda is alkaline in nature, moderately to highly saline and contains high concentration of fluoride. Hundal et al (2007) reported arsenic concentrations greater than the safe limits in water samples from southwest zone of Punjab. Recently, there has been an alarming increase in the number of cancer cases in southwestern districts of Punjab.…”
Section: Introductionmentioning
confidence: 93%
“…Mean arsenic concentrations (10.19 lg/L) found in our study were higher than the arsenic concentrations reported previously in Bathinda, (Sharma 2012) and Amritsar (Hundal et al 2008), but less than the concentrations reported by Sidhu et al 2014 in southwestern region of Punjab. The elevated levels of arsenic in the study area may be due to its evaporative environment since the climate of this region is arid which can lead to more loss of water by evaporation than its gain by rainfall (Hundal et al 2007). Arsenic contamination is also strongly associated with high concentrations of iron, phosphate, and ammonium ions, and anthropogenic activities such as excessive groundwater withdrawal for agricultural irrigation (Kumar et al 2010).…”
Section: Iron and Arsenicmentioning
confidence: 99%
“…Geochemical conditions, such as pH, oxidation-reduction, associated or competing ions, and evaporative environments, have significant effects on arsenic concentration in ground water (Hundal, et al, 2007). The research and studies indicated that sand and clay deposited by river is generally rich in iron and arsenic and the highest arsenic concentration zone exits below 40 meters.…”
Section: Ironmentioning
confidence: 99%